ENTREPRENEURIAL INTEREST AND MOTIVATION AMONG STUDENTS, CASE STUDY OF BEM FIS UNJ BOARD MEMBERS - Pahala, Indra; Fatgehipon, Abdul Haris (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
The research wanted to see the interest and motivation of students, UNJ BEM FIS management in entrepreneurship. Competition in the business world sector is currently getting tighter, however, with the development of information technology providing opportunities that are open to all people to become business actors, advances in the field of digital and information technology have made conventional businesses have to adapt to the digital world, this has created new business opportunities for students, students who are young and generally master the digital world, currently have many roles in business in the digital world. The research method used is descriptive quantitative, the researcher makes an objective picture by using interview data to describe the research findings. Most of the board of BEM FIS UNJ are not aware of the importance of entrepreneurship, even though they have that potential.